PERLAKUAN AKUNTANSI ATAS PENJUALAN KONSINYASI SEBAGAI PIHAK CONSIGNOR PADA CV. “XYZ” di SURABAYA - Diana Zuhroh (AKUNTANSI 45, 2021)
This study aims to discuss the application of accounting treatment for consignment sales as a Consignor at CV "XYZ" as a distributor of Kixx type oil and Fuchs oil in Surabaya. The research approach that I use is a type of qualitative research with descriptive qualitative methods. The types of data include qualitative data and quantitative data, which are taken according to the source using primary and secondary data. The methods of data collection used are interviews, observations, documentation, as well as bibliography searches and online data. The results obtained indicate that the accounting treatment of consignment transactions used by CV. "XYZ" is not to distinguish and not to distinguish between regular sales and sales from consignment, where at the time of delivery of consigned goods sent to the Consignee (commissioner) are treated as ordinary sales in general. Whereas revenue should only be recognized when the goods that have been sent to the Consignee are actually sold to a third party. The impact is that the value of receivables and sales are too large so that the recognized profit will also be too large, while the inventory value shown on the balance sheet shows a number that is smaller than it should be.